Penguatan Literasi Bahaya Zat Adiktif melalui Media Infografis pada Siswa SMA Negeri 2 Banjarbaru: Indonesia - Rasjava, Achmad Ramadhanna'il; Junaidi, Ahmad Budi; Abdullah; Fitria, Rizki; Rahmad, Amalia Fateha; Uzma, Ni'matul (UII, 2026)
High school adolescents are a vulnerable group to exposure to addictive substances due to social and academic pressures, thus requiring literacy-based preventive interventions. This community service program aimed to strengthen students’ literacy regarding the hazards of addictive substances at SMA Negeri 2 Banjarbaru through a chemical literacy-based approach, delivered using educational infographics and participatory learning activities. The program was implemented in a single integrated session consisting of a pre-test, delivery of materials using infographic media accompanied by interactive mini quizzes via Quizizz, a question-and-answer session, and a post-test. A total of 36 students participated in the activity, comprising 12 representatives from each grade level (grades X, XI, and XII). Evaluation results showed an improvement in students’ understanding of addictive substances, as indicated by an increase in the average pre-test score of 66.4 (median 70.0 with score ranged from 30.0 to 100.0) to an average post-test score of 87.5 (median 90.0 with score ranged from 60.0 to 100.0), representing an increase of 21.1 points (31.8%). In addition to quantitative evaluation, brief non-formal interviews with students conducted during and after the activity indicated early signs of changes in students perspectives, particularly in their awareness of adopting healthier and non-addictive coping mechanisms when dealing with academic stress. These findings suggest that infographic-based educational approaches combined with interactive activities are effective in enhancing literacy on the hazards of addictive substances as a foundation for primary prevention among adolescents. To support program sustainability, the educational materials were provided to the school in both printed and digital formats for use in guidance and counseling services as well as school health programs.